Could/should Jubilee debt cancellations be reintroduced today? If not, what alternative measures of debt relief and redistribution might be possible? - Michael Hudson; Charles A. E. Goodhart (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this paper the authors recall the history of Jubilee debt cancellations, emphasizing what their social purpose was at that time. They note that it would not be possible to copy that procedure exactly nowadays, primarily because most debt/credit relationships are intermediated via financial institutions, such as banks, insurance companies, etc., rather than by governments or wealthy families directly. But they argue that the underlying social purpose of such Jubilees - to keep debt within the reasonable ability to be paid without social and economic polarisation - could be recreated via alternative mechanisms, and they discuss the politico-economic arguments for, and against, doing so.
Keywords: E60; E61; E62; E65; H10; H23; H80; N30; N35; P43; Q15; R52; 330; inequality; debt-cancelling jubilees; Babylonian and Byzantine empires; equity participation; student loans; land tax